2009
DOI: 10.1002/nbm.1419
|View full text |Cite
|
Sign up to set email alerts
|

High resolution NMR based analysis of serum lipids in Duchenne muscular dystrophy patients and its possible diagnostic significance

Abstract: Proton NMR spectroscopic investigations on the lipid extract of the serum of 41 Duchenne muscular dystrophy (DMD) (age, mean +/- SD; 8.0 +/- 3.0 years) patients and 22 healthy subjects (age, mean +/- SD; 9.0 +/- 4.0 years) were performed in the northern Indian population. The concentration of triglycerides, phospholipids, free cholesterol, cholesterol esters and total cholesterol was significantly higher in DMD patients as compared to healthy subjects. Ratio of free-cholesterol to cholesterol-esters was also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 35 publications
4
36
0
2
Order By: Relevance
“…Nevertheless, to determine whether the beneficial effects of simvastatin on TA muscle function were associated with reduced circulating cholesterol levels, we measured the plasma LDL and very-low-density lipoprotein (VLDL) as well as HDL cholesterol concentrations. Interestingly, mdx Con mice had significantly higher LDL/VLDL levels than WT mice, in accordance with elevated serum cholesterol levels in DMD individuals (38). However, simvastatin did not lower LDL/VLDL in mdx or WT mice (Fig.…”
Section: Plasma Ldl Cholesterol Is Higher In MDX Mice But Not Reduced Bysupporting
confidence: 60%
“…Nevertheless, to determine whether the beneficial effects of simvastatin on TA muscle function were associated with reduced circulating cholesterol levels, we measured the plasma LDL and very-low-density lipoprotein (VLDL) as well as HDL cholesterol concentrations. Interestingly, mdx Con mice had significantly higher LDL/VLDL levels than WT mice, in accordance with elevated serum cholesterol levels in DMD individuals (38). However, simvastatin did not lower LDL/VLDL in mdx or WT mice (Fig.…”
Section: Plasma Ldl Cholesterol Is Higher In MDX Mice But Not Reduced Bysupporting
confidence: 60%
“…BIO 14.6 animals also exhibited an increase in cholesterol-to-phospholipid ratio in cardiac tissue similar to that observed in UM-X7.1 animals ( 128 ). This increase in cholesterol-to-phospholipid ratio seems to be a common feature of DMD lesions ( 105,129,130 ). It has been proposed that the decrease in phospholipids may be due to the release of phospholipids during the degeneration of muscle as well as the increased activity of phospholipase A in DMD tissue.…”
Section: Muscular Dystrophiesmentioning
confidence: 98%
“…It has been proposed that the decrease in phospholipids may be due to the release of phospholipids during the degeneration of muscle as well as the increased activity of phospholipase A in DMD tissue. During muscle regeneration, increased cholesterol synthesis is required, which may be responsible for the elevated cholesterol levels in DMD patients ( 130 ).…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…When applied to the study of DMD, 1 H magnetic resonance spectroscopy (MRS) has been shown to be an efficient method to identify metabolic changes in muscle and serum, allowing a better understanding of some biochemical processes induced by the disease [17][18][19][20][21][22][23]. In this paper, 1 H high-resolution MRS analysis was used to study two muscles with a different pattern of degeneration in the adult mdx mouse: the diaphragm and the femoral quadriceps.…”
Section: Introductionmentioning
confidence: 99%